Archaeobotanical futures in the Indo‐Pacific. Issue 3 (21st October 2022) - Denham, Tim; Crowther, Alison; Barron, Aleese
Abstract: This paper introduces several archaeobotanical papers published in the same issue of Archaeology in Oceania and presents strongly argued reasons why archaeobotany should become an important subdiscipline within archaeological research in the Indo‐Pacific. RÉSUMÉ: Cet article présente plusieurs articles archéobotaniques publiés dans le même numéro d'Archéologie en Océanie et présente des raisons fortement argumentées pour lesquelles l'archéobotanique devrait devenir une sous‐discipline importante au sein de la recherche archéologique dans l'Indo‐Pacifique.